International Competitiveness of Asian States - Stawicka, Magdalena Kinga (Międzynarodowa pozycja konkurencyjna krajów azjatyckich, 2011)
What is the competitive position of Asian states in the international economy? In order to find the answer, the author shall examine generally-available reports which focus on the competitiveness of states on the grounds of many indexes. For the needs of the present paper the most valid reports are taken into accounts: WEF – The Global Competitiveness Report, IMD – World Competitiveness Yearbook, and Institute of Boao Forum for Asia – Asian Competitiveness Annual Report 2011. Despite differences in terms of a methodology and rating of indexes shaping the competitiveness presented in reports by WEF, IMD, and Boao, the examination shall reflect an outline of the issue and enable a determination of the competitiveness level of the Asia region states.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 192, s. 33-40
Keywords: Asia; competitiveness; IMD; WEF